Neutrophil-to-Lymphocyte Ratio in Predicting Outcomes of Patients with Aneurysmal Subarachnoid Hemorrhage in a Tertiary Care Hospital in Nepal - Rijal, Deepika; Paudel, Sujan; Luitel, Prajjwol; Rijal, Bishwa Deepak; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Journal of Institute of Medicine Nepal, 2025)
Introduction Aneurysmal subarachnoid hemorrhage (aSAH), caused by a ruptured intracranial aneurysm, results in high mortality and disability rates. The Neutrophil-to-lymphocyte ratio (NLR), a simple yet effective marker, holds potential as a valuable prognostic tool, especially in the context of low and middle income countries. The primary aim of study was to predict the outcomes of aSAH patients by modified Rankin Scale (mRS) in 3 months based on admission NLR. Methods This observational study was conducted at Tribhuvan University Teaching Hospital from June 2022 to August 2023. Patients with aSAH presenting to the Emergency Department within 72 hours of symptoms were included. Hematological investigations and non-contrast computed tomography of the head were performed. Outcomes were assessed using the mRS after three months. Results A total of 51 patients were included. The mean age of the study population was 54.1±13.4 years (Range 25 to 80 years). The most common age group was 50-59 years. Female-to-male ratio was 2.9:1 Patients with poor outcomes had significantly higher admission NLR (7.1±4.7) compared to those with good outcomes (3.7±1.9) (p=0.001). Elevated NLR was significantly associated with worse outcomes at three months (p = 0.001). NLR ≥ 3.63 predicted poor prognosis with 87.5% sensitivity. Conclusion This study highlights the utility of NLR in predicting outcomes in aSAH, providing an easy-to-access prognostic marker for risk stratification. The findings are relevant in developing countries, where financial and logistical constraints limit access to advanced neuroimaging and continuous monitoring.